Implikasi Pembatalan Batasan Waktu Pengajuan Grasi Pasca Putusan Mahkamah Konstitusi - Azharie, Ade; Christiawan, Rio; Widyaningrum, Tuti (Widya Yuridika, 2025)
Provisions regarding applications for clemency were previously regulated in Law No. 5 of 2010, then annulled by the Constitutional Court and returned to the norm, which does not provide a time limit for applications for clemency. As a result, for death row inmates, the implementation of court decisions or executions must wait for the convict's request for clemency. The problem that will be studied in this paper is whether the Constitutional Court's decision has implications for hampering law enforcement at the execution stage and resulting in disruption of the element of legal certainty. The research was conducted using a normative juridical research approach with secondary data, which was obtained from library research. If data analysis is described in the form of sentence descriptions and analyzed qualitatively, then a conclusion will be drawn. Based on the research results, it is known that the implication in the execution stage that arises is that there are endless attempts to delay execution, giving rise to uncertainty. The prosecutor, as the executor, experienced difficulties in carrying out the execution of the convict. This delay reduces the deterrent effect on law enforcement. Legal certainty must still be part of the objectives of the law, not just paying attention to justice and benefit alone. Thus, it is still necessary to calculate a reasonable time regarding the deadline for executing the death penalty, especially when the convict or his heirs do not submit a request for clemency.